Chronic hepatitis B prognostic markers other than pre-treatment viral load predicted composite treatment outcome - Myo Nyein Aung; Wattana Leowattana; Khine Nwe Win; Noppadon Tangpukdee; Sant Muangnoicharoen (Journal of Infection in Developing Countries)
Introduction: Chronic hepatitis B (CHB) is a globally common infectious disease. Its clinical course is complicated. In Southeast Asia, nucleos(t)ide analogues (NA) are commonly used drugs for CHB treatment. Composite treatment outcome has often been used in CHB clinical practice, but rarely predicted epidemiologically. This study aimed to compare the composite treatment outcome between CHB patients with low and high treatment-naïve viral load, and to identify its predictors